Implementasi Pendidikan Agama Islam dalam Membentuk Karakter Religius Pemuda Kampung Nyantong Sukaratu Tasikmalaya - Maulana Restu, Yanto; Dika Permana, Muhammad; Zaenudin, Udin; Mubarok, Husni (CV Kalimasada Group, 2024)
This article analyzes how Islamic religious education transforms the character of young people in Kampung Nyantong, Sukaratu, Tasikmalaya into having a religious character. This research method is conducted in a qualitative and descriptive manner with an interview and field observation approach. This article reviews the role of Islamic religious education in transforming young people of Nyantong village into young people who have a religious character and can contribute to various religious social activities in the village such as being a priest of sholat, Friday prayer Khatib, caretaker of bodies, as well as participating in promoting Islamic values in the sphere of the village.